A comparison of the bearing capacity between shallow bucket foundations and solid foundations in clay. (8th August 2020) - Ma, Pengcheng; Liu, Run; Chen, Guangsi; Lian, Jijian; Li, Chengfeng
ABSTRACT: A shallow bucket foundation is a new foundation for offshore wind turbines with advantages of an anti-overturning bearing capacity and differential settlement control. The height-diameter ratio of shallow bucket foundations is less than 0.5. The special structural feature leads to the bucket-soil cooperative bearing mechanism, which is different from the skirts bearing mode of a typical bucket foundation. If stiffness difference between the bucket and the soil is not considered, the bucket and soil are regarded as a whole like a solid foundation. This paper studies difference of failure envelopes between the shallow bucket and solid foundations in clay, derived from three-dimensional finite element analysis. The difference reveals the regularities that the vertical and horizontal ultimate capacities of shallow bucket are better than solid foundation, while the anti-overturning ultimate and multi-ultimate capacities of shallow bucket are worse.